2014
DOI: 10.1080/14615517.2014.941711
|View full text |Cite
|
Sign up to set email alerts
|

Environmental impact assessment of coal mining at Enugu, Nigeria

Abstract: This study determined the views of respondents in Akwuke and Iva mine communities concerning the impact of coal mining activities on animal and plant species, pattern of settlement, pollution effect and health of people living in these two mined areas in Enugu, Nigeria. Data were generated through sample survey using a well-structured questionnaire and personal observation in the field. Khaya ivorensis (mahogany) was the major tree species that had gone extinct (72% of respondents), and Geochelone sulcata (tor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 7 publications
1
11
0
Order By: Relevance
“…Ogbonna et al . () similarly reported that 65% of the respondents from two mining communities of Enugu, Nigeria cited water pollution as the most severe environmental impact of mining in their areas. Nguyen et al .…”
Section: Resultsmentioning
confidence: 96%
“…Ogbonna et al . () similarly reported that 65% of the respondents from two mining communities of Enugu, Nigeria cited water pollution as the most severe environmental impact of mining in their areas. Nguyen et al .…”
Section: Resultsmentioning
confidence: 96%
“…Previously, some economic tree species that were logged from this ecological zone include Canarium schweinfurtii (black pear), Pentaclethra macrophylla (oil bean), Garcinia kola (bitter kola), Vitex doniana (black plum). Milicia excelsa (Iroko) Khaya ivorensis (mahogany) Nauclea diderrichii (Opepe) (Ogbonna et al, 2015). These species have disappeared as none was present in this current study.…”
Section: Discussionmentioning
confidence: 65%
“…To our knowledge, there are no detailed studies documenting the plant species inventories of coal mining sites in Nigeria, especially Enugu (the Nigerian Coal City that used to be home to Iva Valley, Ogbete, Onyeama, and Okpara mines (Sikakwe et al, 2015;Agbalagba and Uzo, 2018). Nonetheless, there is an environmental impact assessment (EIA) report which highlighted the effects of coal mining activities on biodiversity, especially on economic tree species (e.g., Khaya ivorensis and Milicia excelsa) in Akwueke and Iva Valley communities within the Enugu Coal City (Ogbonna et al, 2015). Other previous studies focused instead of floral composition on the geoenvironmental characteristics of the Okpara, Onyeama, and Ribadu coal mine sites (Sikakwe et al, 2015;Sikakwe, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…data). Local extirpations have occurred also in parts of northern Benin, northern Nigeria, central Burkina Faso (where the species was present also in the Ouagadougou region until about 50 years ago), in parts of Mali, Mauritania, and Senegal, and possibly elsewhere (e.g., Ogbonna et al 2015).…”
Section: 6mentioning
confidence: 99%